Anzuelo - Ríos, Emma (Image Comics, 2024)
"The Sea, secretly more complex than anyone imagined, rises one day. The horizon folds as the Sea absorbs the world and transforms everything that's been pulled inside it. Three kids find themselves unmoored and lost, but brought together by the physical and mental changes wrought by the tides and a desire to avoid harming any living creature"--Back cover.